Visible inequality breeds more inequality - Gaechter, Simon (Nature Publishing Group, 2015)
Experiments suggest that when people can see wealth inequality in their social network, this propels further inequality through reduced cooperation and reduced social connectivity. News & Views comment on Nishi et al, Nature 526, 2015, p. 426-429.